Effects of ensiling conditions on pyrrolizidine alkaloid degradation in silages mixed with two different Senecio spp. Issue 2 (4th March 2022) - Klevenhusen, Fenja; These, Anja; Taenzer, Julian; Weiß, Kirsten; Pieper, Robert
ABSTRACT: Pyrrolizidine alkaloid (PA) producing plants like Senecio jacobaea or Senecio vernalis are undesirable in fields for forage production, since PA are toxic to animals and humans. Previous studies have shown that ensiling can decrease the PA content in forages; however, no direct comparison of diverse PA from different Senecio spp. under various ensiling conditions has been made. Therefore, it was hypothesised that individual PA might react differently to ensiling, and silage inoculation with Lactobacillus will affect PA degradation because of a quick drop in pH, contrastingly to poor silage qualities resulting from contamination with soil. Laboratory scale grass silages were prepared in a multifactorial design with two levels of dry matter contents, four ensiling treatments and two storage durations (10 and 90 d). For each combination, four replicates were prepared individually. Ensiling treatments were (1) 10 ml water per kg fresh matter as control (CON), (2) 10 ml heterofermentative Lactobacillus buchneri strain LN4637 at 3 · 10 5 cfu/kg fresh matter plus 25 g molasses/kg fresh matter (LBHE), (3) 10 ml homofermentative lactobacilli at 3 · 10 5 cfu/kg fresh matter plus 25 g molasses/kg fresh matter (LBHO) and (4) 10 g soil/kg fresh matter (SOIL). Treatments affected formation of fermentation acids. Acetic acid was highest with treatment LBHE, and butyric acid was highest with treatment SOIL. All ensiling treatments effectively reduced total PA content by degrading the PA N -oxide (PANO) fraction. In parallel, though, the fraction of the tertiary base forms increased by around one-tenth of the original PANO content. Contents of jaconine and senkirkine were higher after ensiling than before, with regards to the sum of PA and PANO for jaconine, indicating higher stability or new formation through degradation of other PA. Overall, ensiling offers opportunities to decrease the PA-PANO content in feed and therefore lowers the risk of intoxication by Senecio in livestock.